PERENCANAAN BIAYA DAN METODE PELAKSANAAN PADA JALAN PAMEU-GENTING GERBANG KABUPATEN ACEH TENGAH - Faizal Bakrie (Portal: Jurnal Teknik Sipil, 2016)
Cost Planning is planning a number of calculations necessary costs for material, labor, equipment and expenses related in implementation of the project Construction  and  Implementation  Method  road  is  a  basic  reference  in  the implementation of road construction by Standard Highways applied to the road Pameu- Genting Gate starting from the STA 45 + 850 s I d 49 + 500. Calculation of Budget Plan include Job Layers Base Down (LPB) Aggregate B, Works layer Piling Up (LPA) Aggregate A, (Prime Coat), Works Layer Binder AC-BC and Layer Aus AC-WC  (Surface). The method used is Estimation Method Index (E.l) Highways, 2010. From the calculation results obtained execution time of 166 working days,fee for Base Aggregate Base Layer B Amounting Rp.4. 032.876,00, -. Costs for Top Layer Aggregate Base A sum Rp.3.376.312,816.50, -. Fees for absorbing binder layer of Rp. 122,801,512.50, - Fees for Layers Between AC-BC (Surface) of Rp. 4. 732.319.951.10, - and the cost for AC-WC Aus layer Rp.2.331.857.250.00 So the sum total budget is of Rp. 14,752,380,906.00, - the value added tax (VAT) of 10% as well as the scheduling of the execution time using the S curve. and the method of implementation applied to the project include Job Layers Base Down Aggregate B, Layer Piling Up Aggregate A, (Prime Coat), Layer Binder AC-BC and and the cost for AC-WC (Surface) with a systematic way, accuracy, effective and efficient based on the plans.Keywords: Budget Plan, S curve, and Methods of Implementation